NATIONALISM AND MULTICULTURALISM IN ISLAMIC PERSPECTIVE ON INDONESIAN LITERARY NOVELS IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Haris Supratno, Resdianto Permata Raharjo, Dedy Rahman Prehanto, Aries Dwi Indriyanti (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purposes of this research is finding and describing the representation of nationalism including thought, love, peace, freedom, and loyalty actions to the country, reflected on Indonesian literary novels in 2000s. This research used qualitative method. The data sources of this research are Indonesian literary novels in 2000s. The data collection technique used library or documentation techniques from 2000s Indonesian literary novels. The data are analyzed by descriptive analysis techniques and content analysis. While the technique for testing the validity of data used trust, traceability, dependence, and certainty. The results of this research showed that Indonesian literary novels in the 2000s represent nationalism which includes: (1) nationalism related to the idea of creating a new, fair, and prosperous society. To be able to realize a fair and prosperous society, people must have basic needs for clothing, food, housing, (2) nationalism related to love and pride for Indonesia as a nation and the Unitary State of the Republic of Indonesia, and (3) nationalism related to actions to prevent conflicts, polemics, and wars between countries, because the society of one nation who will suffer the most due to be the victims. The results of this research is hoped to encourage and strengthen the sense of nationalism of Indonesian people, especially the younger generation, to continue the thoughts of proud and loving as the part of Indonesian nation and the Unitary State of the Republic of Indonesia, and always ready to develop this country as well as to defend the Indonesian homeland from all threats, both from inside and outside the country. A strong thought of Indonesian nationalism will be able to prevent negative impacts on advances in information technology in the Industrial Revolution 4.0. era.